Cost-effectiveness analysis of Dapagliflozin versus Canagliflozin in treatment of type 2 diabetes mellitus - Sadagoban Gopal Krishnamoorthy, Jemi Rachel Shaji, Bhagya Premnath, Akshitha Rani Siby, Swathi Swaroopa Borra , Ayilya Manomohan, Arun Kanniyappan Parthasarathy (Journal of Applied Pharmaceutical Science, 2022)
The objective of this study was to provide cost-effectiveness evidence regarding the use of Dapagliflozin 10 mg and Canagliflozin 300 mg for treating adult patients with type 2 DM by measuring the clinical outcomes of the selected treatment regimens and by conducting a decision analysis. The main considered outcomes were cost, probabilities of diabetic complications, life year (LY), quality-adjusted life year (QALY), and incremental cost effectiveness ratio. Oneway deterministic sensitivity analysis was also carried out. Cost effective analysis was carried out and Dapagliflozin was found to be more effective and less expensive which apparently falls on Q4 North West Position. In this study, better results were found with the control group (A) Dapagliflozin than the comparison group (B) Canagliflozin. We assume that the economical and clinical outcomes of Pharmacoeconomics were affected by various other factors like medication adherence, affordability, appropriateness of regimens, and other social and cultural factors. Further studies should be conducted on these matters to understand and improve the QALY and also to reduce the burden of disease of type 2 diabetic patients.
Keywords: Health outcome research, CEA of Canagliflozin, CEA of Dapagliflozin, cost effective analysis, pharmacoeconomic analysis